NONFINANCIAL AND FINANCIAL DETERMINANTS OF CORPORATE FINANCIAL PERFORMANCE - KAREN AZIZAH; ARLEEN HERAWATY (Jurnal Bisnis dan Akuntansi, 2017)
In today’s competitive corporate world, financial performance of a company becomes an essential part in determining the company’s sustainability in a long run. However, stakeholders do not only focus on the financial determinants that made up a company’s financial performance as awareness on human rights along with the environmental-friendly products and community activities done by the company are also on a lookout. Moreover, in a developing country with such volatile economy like Indonesia very little research has been done regarding the influence of corporate’s financial performance. The objective of this research is to analyze the influence of corporate social activities dimensions denoted as community involvement disclosure, employee relation disclosure, environment disclosure, and product disclosure as well as leverage, debt ratio, sales growth and firm size to support the possible financial determinants to corporate financial performance in Indonesia’s listed nonfinancial companies. Population in this research is all listed nonfinancial companies in Indonesia Stock Exchange during 2011 to 2015. Samples are obtained through purposive sampling method, in which 169 listed nonfinancial companies in Indonesia Stock Exchange met the sampling criteria resulting in 845 data available as sample. Multiple linear regressions and hypothesis testing are used as the data analysis method in this research. The result of this research shows product disclosure and debt ratio are statistically influencing corporate financial performance of listed nonfinancial companies in Indonesia. In contrary, community involvement disclosure, employee relation disclosure, environment disclosure, leverage, sales growth and firm size do not statistically influence the corporate financial performance of listed nonfinancial companies in Indonesia during the research period.